Shadows of Empire: Post-Soviet Para-States in Russian Grand Strategy - Hardy, John; Vlad, Ruxandra Oana (Journal of Regional Security, 2024)
The post-Soviet period has seen dramatic political upheaval across Eastern Europe and the Caucuses. The shadow cast by centuries of Russian influence on Eurasia still affects political tensions in the region. Previous studies have examined both Russian foreign policy in the twenty-first century and the implications of parastates on Russia’s periphery. This study focuses on the intersection of these issues, identifying parastates as a political wedge used by Moscow to maintain buffer states between its borders and NATO. It presents a comparative analysis of three parastates that are supported by Russia: Transnistria in Moldova, Abkhazia and South Ossetia in Georgia, and Nagorno-Karabakh in Azerbaijan. The study finds that Russia supports post-Soviet parastates to perpetuate political stalemates that undermine stability in countries that act as buffers between Russian and NATO borders. This highlights opportunities for further research on a foreign policy tool that can be used to significantly influence regional security.